2020
DOI: 10.1109/tpds.2020.2967662
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Workflow Simulation on Clouds based on Computation and Communication Noisiness

Abstract: Many researchers rely on simulations to analyze and validate their researched methods on Cloud infrastructures. However, determining relevant simulation parameters and correctly instantiating them to match the real Cloud performance is a difficult and costly operation, as minor configuration changes can easily generate an unreliable inaccurate simulation result. Using legacy values experimentally determined by other researchers can reduce the configuration costs, but is still inaccurate as the underlying publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Similarly, to minimize uncertainty propagation in scheduling workflows, Chen et al [20] model task execution time and data transfer time by means of normal distributions. Mathà et al [33] include performance instability in cloud simulation environments by introducing the concept of noise in computation and communication tasks. Performance data monitored in real cloud environments are the basis for extracting the noise.…”
Section: B Performance Uncertaintymentioning
confidence: 99%
“…Similarly, to minimize uncertainty propagation in scheduling workflows, Chen et al [20] model task execution time and data transfer time by means of normal distributions. Mathà et al [33] include performance instability in cloud simulation environments by introducing the concept of noise in computation and communication tasks. Performance data monitored in real cloud environments are the basis for extracting the noise.…”
Section: B Performance Uncertaintymentioning
confidence: 99%
“…In Reference 10, the authors showed that the bandwidth depends on the file sizes, number of files, instance types, and so forth. But our simulations assume a good QoS and the respect of the performance characteristics for the resources allocated by the cloud provider.…”
Section: Platform and Application Modelsmentioning
confidence: 99%